The new evidence act 2011: type or shadow of the old act? (2013)
The Evidence Act in Nigeria has witnessed a lot of changes. The question however is whether the changes are in form or content. The paper traced the history of the repealed 2004 Act from when it was enacted to when it was repealed and also discussed the passing of the 2011 Act. A detailed comparison between the two Acts was done under different subtitles. The distinctive features of the 2011 Act was carefully brought out. The paper went on to consider if the 2011 Evidence Act is another attempt at a cosmetic change or an inferior remnant of the repealed 2004 Act. This finally answered the question if it is a type or shadow? The author then answered the burning question “so what is even new in the 2011 Evidence Act". The paper ends with a conclusion and made recommendations for further works on the 2011 Act.